(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2025)
The study investigated Relationship Between Staff Remuneration And Academic Staff Productivity In Universities Of Northeast Nigeria. To guide the study, 2 specific objectives were focus of the study. The study answered 2 research questions and tested 2 hypotheses at 0.05 level of significance. The study adopts correlational research design with a population of 2600 academic staff. The sample size of the study was 780 drawn using multistage sampling. The instrument used was developed by the researcher and tagged ‘Remuneration and welfare packages questionnaire (RAWPQ). The researcher used inferential statistics of mean and standard deviation to answer the research questions, The mean score above 2.5 indicates high academic staff productivity while the mean score below 2.5 indicates low academic staff productivity while linear regression was used to test the hypotheses at 0.05 level of significance. Data generated from the study were analyzed using descriptive and inferential statistics. Descriptive statistics of mean and standard deviation were used to answer the research questions while inferential statistics of Pearson Product Moment Correlation (PPMC) and independent t-test was used to test the null hypotheses. Based on the analysis study findings are; staff salary, earned academic allowance, promotion, pension, housing, medical health insurance has significant relationship on academic staff productivity among staff of State Universities in North East, Nigeria. Recommendations were made among others that State Universities in North East Nigeria should prioritize timely and adequate payment of staff salaries, payment of earned allowances, and establish clear policies on promotion benefits to motivate staff for enhanced productivity .